a study on the supply chain and market selection dilemnas of indian diamond industry - Mahajan, Varun (2007)
This study aims to investigate the underlying dilemmas that exist in the Indian diamond industry, which is presently standing at a cross-road, where the retail demand of Indian diamonds in foreign as well as in the domestic markets have turned slack due to inappropriate ÃÂsupply chain management and market selection practices. In order to capture the various issues faced by the industry players, literature review on the key components of SCM, in context of Indian diamond industry supply chain and market selection has been focused.